Enhancing Student Engagement and Active Learning in Online Learning Environments: Lesson Learnt During the COVID-19 Lockdown - Chitanana, Lockias (IGI Global, 2022)
COVID-19-related closures of educational institutions have prompted universities around the world to mobilize remote learning solutions to ensure educational continuity. Universities were swift in their response and provided multiple remote learning solutions including different forms of online learning to reach students during university closure. This chapter discusses a study that explored the lived experiences of university lecturers who participated in online teaching during the pandemic. These experiences help us to draw lessons that can inform us about the quality of student engagement during online learning. An actor-network theory-informed study design method was used to follow the actors in action. The data was collected through a mixture of data collection including semi-structured interviews, observations, and documents analysis. The analysis shows that online learning was the main method of instruction deployed by universities in Zimbabwe during the pandemic. Lecturers reported a wide range of online learning experiences engaging students in active learning.